2014
DOI: 10.1007/s00018-014-1683-3
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in cancer progression

Abstract: Neutrophils are being increasingly recognized as an important element in tumor progression. They have been shown to exert important effects at nearly every stage of tumor progression with a number of studies demonstrating that their presence is critical to tumor development. Novel aspects of neutrophil biology have recently been elucidated and its contribution to tumorigenesis is only beginning to be appreciated. Neutrophil extracellular traps (NETs) are neutrophil-derived structures composed of DNA decorated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
204
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(216 citation statements)
references
References 107 publications
(358 reference statements)
3
204
0
9
Order By: Relevance
“…Accumulating evidence indicates that solid tumors frequently display an inflammatory microenvironment [51,89], characterized by large numbers of tumor-associated neutrophils, which play an important role in cancer progression and angiogenesis [90][91][92]. The role of the crosstalk between cancer cells and stromal cells in tumor growth, metastasis, as well as response to antitumor therapy [93][94][95][96] and the tumor promoting activities of fibroblasts, which are the most abundant cells in the tumor stroma, are also well established [97].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that solid tumors frequently display an inflammatory microenvironment [51,89], characterized by large numbers of tumor-associated neutrophils, which play an important role in cancer progression and angiogenesis [90][91][92]. The role of the crosstalk between cancer cells and stromal cells in tumor growth, metastasis, as well as response to antitumor therapy [93][94][95][96] and the tumor promoting activities of fibroblasts, which are the most abundant cells in the tumor stroma, are also well established [97].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cools-Lartigue and colleagues reported that neutrophil-released neutrophil extracellular traps (NET) can contribute to cancer metastasis (94). NETs are neutrophil-derived structures composed of DNA, chromatin, and granule proteins and represent a host defense mechanism by trapping and killing microorganisms (95). Circulating tumor cells become trapped within NETs, and NET trapping increases formation of liver metastasis (94).…”
Section: Neutrophils In Premetastatic and Metastatic Microenvironmentsmentioning
confidence: 99%
“…Another interesting observation in this context, connecting the coagulation and innate immune systems, is the fact that neutrophil extracellular traps (NET) have been found to play a role in malignant progression (6,7). NETs were identified in 2004 (8) and are extracellular networks that primarily consist of DNA released from neutrophils together with antimicrobial peptides and proteases derived from neutrophil granules.…”
Section: Introductionmentioning
confidence: 99%